1980
DOI: 10.2466/pr0.1980.47.3f.1043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Controversy and Defensiveness on Cognitive Perspective-Taking

Abstract: 45 undergraduates discussed a moral issue with a confederate who had the same opinion (no controversy) or opposite opinion (controversy). Subjects in the conditions with controversy were induced to have a high level of defensiveness by a disconfirmation of personal competence or a low level of defensiveness by a confirmation. Subjects in no controversy experienced confirmation. Subjects in the condition of confirm controversy indicated mote conceptual conflict (uncertainty) and were more accurate in taking the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 11 publications
0
27
0
1
Order By: Relevance
“…Tjosvold (1985) defines controversy as a "special kind of conflict that occurs when one person's ideas, opinions, conclusions, theories, and information are incompatible with another's when they discuss problems and make decisions" (p. 22). Several studies conducted by Tjosvold and his colleagues have found that controversy motivates people to know others' positions and to develop understanding and appreciation of them (Tjosvold & Johnson, 1977, 1978Tjosvold, Johnson, & Fabrey, 1980;Tjosvold, Johnson, & Lerner, 1981). There is also some evidence suggesting that controversy results in open-mindedness, interpersonal attraction, and incorporation of opposing views into one's own (Tjosvold, 1982;Tjosvold & Deemer, 1980).…”
Section: Research On Benefits From Cognitive Conflictmentioning
confidence: 99%
“…Tjosvold (1985) defines controversy as a "special kind of conflict that occurs when one person's ideas, opinions, conclusions, theories, and information are incompatible with another's when they discuss problems and make decisions" (p. 22). Several studies conducted by Tjosvold and his colleagues have found that controversy motivates people to know others' positions and to develop understanding and appreciation of them (Tjosvold & Johnson, 1977, 1978Tjosvold, Johnson, & Fabrey, 1980;Tjosvold, Johnson, & Lerner, 1981). There is also some evidence suggesting that controversy results in open-mindedness, interpersonal attraction, and incorporation of opposing views into one's own (Tjosvold, 1982;Tjosvold & Deemer, 1980).…”
Section: Research On Benefits From Cognitive Conflictmentioning
confidence: 99%
“…He defines controversy as a "special kind of conflict that occurs when one person's ideas, opinion, conclu sions, theories, and information are incompatible with another's when they dis cuss problems and make decisions" (p. 22). Several studies have found that controversy motivates people to know others' positions and to develop under standing and appreciation of them , 1978Tjosvold, Johnson, & Fabrey, 1980;Tjosvold, Johnson, & Lerner, 1981). Also, contro versy may result in open-mindedness, interpersonal attraction, and incorpora tion of opposing views into one's own (Tjosvold, 1982;Tjosvold & Deemer, 1980).…”
mentioning
confidence: 99%
“…Camper sur sa position et refuser d'intégrer les positions alternatives (Johnson et al, 1990 ;Tjosvold, 1998 ;Tjosvold & Deemer, 1980) La remise en cause des compétences propres peut en ce sens être particulièrement mal vécue. En effet, des recherches ont montré que lorsque la compétence des participants est remise en cause par leur partenaire lors de confrontations de points de vues divergents, ils expriment plus d'incertitude relative à leur compréhension, mais également plus de détresse interne ; ils déprécient leur partenaire de manière plus importante, tout en indiquant une plus grande fermeture d'esprit que les participants dont les compétences sont confirmées (Tjosvold, Johnson & Fabrey, 1980) ou que ceux pour lesquels aucune évaluation des compétences n'est mentionnée (Tjosvold, Johnson & Lerner, 1981). De même des étudiants qui reçoivent des critiques non constructives sur leur travail (évaluation négative non spécifique et attribuée à des causes internes) rapportent plus de colère et de tension avec une volonté plus grande de résister et d'éviter l'évaluateur que ceux qui reçoivent une évaluation négative avec des critiques constructives (Baron, 1988).…”
Section: Le Manque De Participation Réciproqueunclassified